Exsolution of Ni nanoparticles on the surface of cerium and nickel co-doped lanthanum strontium titanate as a new anodic layer for DIR-SOFC. Anti-coking potential and H2S poisoning resistance of the prepared material. (30th October 2020) - Błaszczak, Patryk; Łapiński, Marcin; Wang, Sea-Fue; Jasiński, Piotr; Bochentyn, Beata
Abstract: The aim of this study was to evaluate a new catalytic material for biogas-fuelled DIR-SOFCs. This material was a perovskite-type SrTiO3 doped with La, Ce and Ni of a general formula La0.27 Sr0.54 Ce0.09 Ni0.1 Ti0.9 O3-σ (LSCNT). Additional preparation steps were undertaken to promote a nickel exsolution process. Heat post-treatment of powders in a humidified H2 resulted in an intensive growth of nickel nanoparticles (NPs) while the reduction temperature was increased gradually from 800 to 1200 °C. A selected reduction temperature equal to 900 °C gave the NPs an average size of 22 nm. The prepared material was used as a functional layer deposited onto the anodic site of a Ni/YSZ-supported SOFC to promote the effective reforming of synthetic and H2 S-contaminated biogas at 750 °C. It was found that after 130 h of operation in a 60% CH4 /40% CO2 mixture, the fuel cell with an additional LSCNT layer showed higher power density, and no carbon deposits were observed. However, 20 ppm of H2 S present in the fuel caused a full deactivation of both the reference and SOFC with LSCNT layer. Cyclic tests in sour biogas revealed that the fabricated anodic layer is much more resistant to sulfur poisoning compared to a bare Ni/YSZ anode. Recovery of overall performance after 3 poisoning cycles was nearly 90% for the fuel cell with the LSCNT layer, while the unmodified one reached only 75%. The concentrations of the exhaust gases, such as CH4, CO2, and CO, were continuously measured in situ using a FTIR-based technique. A thermochemical analysis revealed that the investigated material ensured much better biogas reforming stability over the whole testing time and strongly promoted catalytic reactions. Highlights: La0.27 Sr0.54 Ce0.09 Ni0.1 Ti0.9 O3-σ (LSCNT) anodic layer for DIR-SOFC was prepared. Performance in hydrogen, synthetic and sulfur-contaminated biogas was examined. Anode with LSCNT layer is more stable and lowers the overall cell degradation.